2015
DOI: 10.32404/rean.v2i1.248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminum on Seed Germination and Initial Growth of Physic Nut Seedlings

Abstract: Aluminum (Al 3+) toxicity is one of the major factors that limit plant growth and crop yield in acid soils. The phytotoxic effects of aluminum on the seed germination and initial growth of physic nut (Jatropha curcas L.) seedlings were investigated in the present study. Physic nut seeds were subjected to five levels of aluminum [0 (control), 20, 40, 60 and 80 mg L-1 ], using the solution-paper method, with eight replications. The experimental unit consisted in a germitest paper roll with 25 physic nut seeds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
1
0
3
Order By: Relevance
“…Nevertheless, even with the reduction in germination by the toxic effect of aluminum, this was superior to 25%, and it can be considered elevated for a weed plant, demonstrating the capacity of adaptation of this to that adverse conditions (Zhao et al 2017). Similar results were observed in Conyza bonariensis and C. canadenses, when the seeds were put to germinate in moistened substrate with solutions of aluminum from zero to two cmolc L -1 , occurring reduction of germination in concentrations superior to 1.5 cmolc L -1 (Yamashita & Guimarã es, 2011 (Gallon, 2015), Jatropha curcas (Machado et al 2015) and Hancornia speciosa (Rodrigues et al 2017).…”
Section: Resultsmentioning
confidence: 65%
“…Nevertheless, even with the reduction in germination by the toxic effect of aluminum, this was superior to 25%, and it can be considered elevated for a weed plant, demonstrating the capacity of adaptation of this to that adverse conditions (Zhao et al 2017). Similar results were observed in Conyza bonariensis and C. canadenses, when the seeds were put to germinate in moistened substrate with solutions of aluminum from zero to two cmolc L -1 , occurring reduction of germination in concentrations superior to 1.5 cmolc L -1 (Yamashita & Guimarã es, 2011 (Gallon, 2015), Jatropha curcas (Machado et al 2015) and Hancornia speciosa (Rodrigues et al 2017).…”
Section: Resultsmentioning
confidence: 65%
“…Aluminum stress negatively affected seed germination and seedling vigor of Arctium lappa L. (Silverio et al, 2021). Machado et al (2015), when evaluating the germination of Jatropha curcas L. seeds exposed to five concentrations of Al, found that the element reduced germination by up to 90%, in addition to reducing 76 and 83% of the length and dry matter of the roots of the seedlings., respectively. In the literature, authors observed that some species also had root growth inhibition in response to Al toxicity, as in Phaseolus vulgaris L. (Domingues et al, 2013), Trifolium pretense L. (Scheffer-Basso and Prior, 2015) and Lactuca sativa L. (Silva and Matos, 2016).…”
Section: Germination and Seed Vigor Of Phaseolus Vulgaris Submitted T...mentioning
confidence: 99%
“…Semakin tinggi konsentrasi ion Al dalam tanah maka semakin rendah pH tanah (Salam, 2012), Pada pH tanah rendah sekitar 4,3 bentuk Al yang melimpah adalah aluminium trivalent (Al 3+ ) dan sangat berdampak negatif terhadap pertumbuhan tanaman (Bojorquez- Quintal et al, 2017). Machado et al (2015) Berdasarkan hasil penelitian, perlakuan Al pH 4,5 pada perkecambahan memberikan respons paling buruk terhadap vialbilitas dan vigor tujuh varietas benih kedelai. Hal ini ditunjukkan dari muncul radikula pertama pada hari ke-1 media Al pH 4,5 sebesar 78,57% dibandingkan Al pH 6-7 sebesar 85,90% dan kontrol 90,76%.…”
Section: Pendahuluanunclassified